2021
DOI: 10.3390/a14030083
|View full text |Cite
|
Sign up to set email alerts
|

Typhoon Intensity Forecasting Based on LSTM Using the Rolling Forecast Method

Abstract: A typhoon is an extreme weather event with strong destructive force, which can bring huge losses of life and economic damage to people. Thus, it is meaningful to reduce the prediction errors of typhoon intensity forecasting. Artificial and deep neural networks have recently become widely used for typhoon forecasting in order to ensure typhoon intensity forecasting is accurate and timely. Typhoon intensity forecasting models based on long short-term memory (LSTM) are proposed herein, which forecast typhoon inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Due to artificial control and natural factors, such as sluices, pumps, rainfall, and tides, the variations in river water levels are highly uncertain [29]. Therefore, it is necessary to consider the rolling forecast method [30][31][32][33]. In this study, the river section water levels were forecast by the rolling forecast method, as shown in Figure 3.…”
Section: Real-time Rolling Forecast Methods and Implementationmentioning
confidence: 99%
“…Due to artificial control and natural factors, such as sluices, pumps, rainfall, and tides, the variations in river water levels are highly uncertain [29]. Therefore, it is necessary to consider the rolling forecast method [30][31][32][33]. In this study, the river section water levels were forecast by the rolling forecast method, as shown in Figure 3.…”
Section: Real-time Rolling Forecast Methods and Implementationmentioning
confidence: 99%
“…BPESN performs the best among all the contrasts in view of the data distribution, median, and mean, indicating that the prediction ability of the BPESN model is the best. for i in mappingNum: (2) for j in enhanceNum: (3) enter data into the mapping layer and initialize it W ej , β ej and get the matrix Z; (4) initialize the ESN of the reinforced layer, collect the calculation result matrix H; (5) each ESN is pruned and optimized, and the RMSE after optimization is calculated and record the number of pruning C; (6) if RMSE < thresholdRMSE or C < thresholdPrunNum: (7) Add unpruned ESN units into the reinforced layer for further pruning; (8) else: (9) Calculation of the same mapping layer different enhancement layer ESN pruning optimized performance index; (10) end (11) end (12) the optimized parameters and predicted output are calculated. ALGORITHM 1: BPESN with pruning optimization.…”
Section: Prediction Of Air Quality Monitoring Datamentioning
confidence: 99%
“…e stock data prediction can foresee the capital flows trend [2]. e precipitation [3], water bloom [4], and typhoon intensity are also predicted for natural environment protection and disaster prevention [5]. e trend forecast of air pollutants provides strong support for the decisionmaking of relevant departments in the future [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al (2018) pointed out that the percentage and annual average intensity of TCs that landed in East Asia and Southeast Asia have increased significantly between 1974 and 2013. Yuan et al (2021) developed a long and short-term memory (LSTM) TC intensity prediction model on the basis of artificial neural networks; the model can provide meaningful results for the prediction of TC intensity within 120 hours. Liou et al (2018) found that the winter cold front affects TC tracks and increases TC intensities.…”
Section: Introductionmentioning
confidence: 99%